Tracing the Diploid Ancestry of the Cultivated Octoploid Strawberry. (17th September 2020) - Feng, Chao; Wang, Jing; Harris, A J; Folta, Kevin M; Zhao, Mizhen; Kang, Ming
Abstract: The commercial strawberry, Fragaria × ananassa, is a recent allo-octoploid that is cultivated worldwide. However, other than Fragaria vesca, which is universally accepted one of its diploid ancestors, its other early diploid progenitors remain unclear. Here, we performed comparative analyses of the genomes of five diploid strawberries, F. iinumae, F. vesca, F. nilgerrensis, F. nubicola, and F. viridis, of which the latter three are newly sequenced . We found that the genomes of these species share highly conserved gene content and gene order. Using an alignment-based approach, we show that F. iinumae and F. vesca are the diploid progenitors to the octoploid F. × ananassa, whereas the other three diploids that we analyzed in this study are not parental species. We generated a fully resolved, dated phylogeny of Fragaria, and determined that the genus arose ∼6.37 Ma. Our results effectively resolve conflicting hypotheses regarding the putative diploid progenitors of the cultivated strawberry, establish a reliable backbone phylogeny for the genus, and provide genetic resources for molecular breeding.